A novel process for transcellular hemoglobin transport from macrophages to cancer cells - Agata Braniewska; Marcin Skorzynski; Zuzanna Sas; Magdalena Dlugolecka; Ilona Marszalek; Daria Kurpiel; Marcel Bühler; Damian Strzemecki; Aneta Magiera; Maciej Bialasek; Jaroslaw Walczak; Lukasz Cheda; et al. (Cell Communication and Signaling)
Abstract Hemoglobin (Hb) performs its physiological function within the erythrocyte. Extracellular Hb has prooxidative and proinflammatory properties and is therefore sequestered by haptoglobin and bound by the CD163 receptor on macrophages. In the present study, we demonstrate a novel process of Hb uptake by macrophages independent of haptoglobin and CD163. Unexpectedly, macrophages do not degrade the entire Hb, but instead transfer it to neighboring cells. We have shown that the phenomenon of Hb transfer from macrophages to other cells is mainly mediated by extracellular vesicles. In contrast to the canonical Hb degradation pathway by macrophages, Hb transfer has not been reported before. In addition, we have used the process of Hb transfer in anticancer therapy, where macrophages are loaded with a Hb-anticancer drug conjugate and act as cellular drug carriers. Both mouse and human macrophages loaded with Hb-monomethyl auristatin E (MMAE) effectively killed cancer cells when co-cultured in vitro.